II.

  1. A.
  2. I
  3. I. 10. .
  4. I.
  5. I. , '
  6. I.
  7. I. ֳ

(2 )

1. -

1.
2.
3.
4.
5.
6.
7.
8.
9.
10.

2.

1. ;
2. ;
3. ;
4. ;
5. ;
6. ;
7. ;
8. ;
9. ;
10. ;

3. , 1 2

1 2
y = x2- 2x+ 3 y= 3x- 1
y = x2+ 2x- 5 y= 5 - x
y = x2 - x- 4 y= 3x- 7
y = x2+ 12x+ 15 y= - x2+2x+ 3
y = x2- 2 y= 2, x = - 1 x = 1
y = - x2+ 3x + 6 y = x2- X + 1
y = x2+ 2x+ 3 y = x+ 9
y= 3x2+ 5 y= 2x2+ 6x- 10
y = x2 - 8x+ 1 y= 2x+ 8
y= 3x2+ 2 y= 7, x = 0 x = 1

4. :

- ;

- ;

- .

1.
2.
3.
4.
5.
6.
7.
8.
9.
10.

5. 䳺 U :

U
1. (2, 1)
2. (3, 5)
3. (-1, 4, 2)
4. (1, 0, 1)
5. (2, 2, 2)
6. (0, -1, 1)
7. (1, 2, 3)
8. (3, 2, 1)
9. (-1, 3, 1)
10. (0, 1)

6. - :

-
1.
2.
3.
4.
5.
6.
7.
8.
9.
10.

7. :

1.
2.
3.
4.
5.
6.
7.
8.
9.
10.

8. f(x) x - a:

1. f(x) = x3- 2x2+ 3x
2. - 2
3. f(x) = x4- 5x3 + x2+ 2
4.
5. f(x) = x5- 2x3 - x+ 6 - 2
6. - 3
7. f(x) = 2x3+ 3x2- 2x- 3
8.
9. f(x) = x6- 3x2+ 5x- 2
10.


I. | III.
© um.co.ua -